Pravljice, ki jih mladi straši pripovedujejo, pravljice, ki jih otroci poznajo - Štefan, Anja (Znanstvena založba Filozofske fakultete, 2021)
V prispevku avtorica na podlagi svojih pripovedovalskih izkušenj in na podlagi ankete, ki jo je opravila med slovenskimi tretješolci, razmišlja o poznavanju folklornih pripovedi in prisotnosti pripovedovanja v slovenskih mladih družinah. Opaža, da zavzemajo folklorne pripovedi med vsem ostalim čtivom, ki se ga otrokom ponuja ali ki si ga izbirajo sami, razmeroma majhen delež. K razširjenosti in prepoznavnosti folklornih pripovedi bistveno pripomorejo objava v slikanici, na CD-ju in v berilu. Med družinskimi člani, ki otrokom posredujejo pripovedi, izrazito izstopa mama. Pripovedovanje otroci omenjajo predvsem v zvezi s pravljicami, ki si jih odrasli izmišljujejo zanje - bodisi pred spanjem ali v povezavi s skupnim delom. Pripovedovanja, ki bi nadaljevalo verigo ustnega prenašanja slovenskih pripovedi, skoraj ni več zaznati. Neznatna znamenja, ki vendarle kažejo v to smer, bi bilo vredno raziskati. On the basis of her storytelling experience and a survey carried out among Slovene third graders, the author reflect on awareness of folk tales and the presence of storytelling in young Slovene families. She notes that folk tales make up a relatively small part of the reading material that is offered to children. For greater awareness and wider dissemination of these stories, it On the basis of her storytelling experience and a survey carried out among Slovene third graders, the author reflect on awareness of folk tales and the presence of storytelling in young Slovene families. She notes that folk tales make up a relatively small part of the reading material that is offered to children. For greater awareness and wider dissemination of these stories, it is crucial that they appear as picture books, on CD and in readers. The memberof the family who is by far the most likely to tell stories to children is the mother. Storytelling is most often mentioned in connection with made-upfairy stories told to children at bed time or in connection with some shared task. Nowadays, the kind of storytelling that would continue the tradition of oral transmission of Slovene tales has almost disappeared. But the faint signs that point in that direction would certainly be worth researching. is crucial that they appear as picture books, on CD and in readers. The member of the family who is by far the most likely to tell stories to children is the mother. Storytelling is most often mentioned in connection with made-upfairy stories told to children at bed time or in connection with some shared task. Nowadays, the kind of storytelling that would continue the tradition of oral transmission of Slovene tales has almost disappeared. But the faint signs that point in that direction would certainly be worth researching.